Economic evaluation of intravenous iron formulations for patients with iron deficiency anemia: a systematic review - Xing, Zhicong; Mu, Shengjun; Xue, Qingxia; Sun, Fudong; Hou, Guige; Zhao, Quan (Frontiers in Health Services, 2025)
BackgroundVarious intravenous iron formulations show great promise in the treatment of iron deficiency anemia (IDA), and economic evaluation results are becoming increasingly important as criteria for allocating healthcare resources. This study aimed to systematically evaluate the economics of six main intravenous iron formulations in the treatment of IDA.MethodsComputerized search of relevant studies in PubMed, Embase, Web of Science, and The Cochrane Library to collect economic evaluation of six intravenous iron formulations for the treatment of patients with IDA; the time limit for searching was from the establishment of the database to 30 July 2025. Two reviewers independently screened literature, extracted data, evaluated the quality of included studies using the Consolidated Health Economic Evaluations Reporting Standards 2022, and performed descriptive analyses.ResultsOf the 2,288 articles retrieved, 17 studies were included, including five drugs, conducted in 10 different countries. Six studies compared ferric carboxymaltose (FCM) with iron sucrose (IS); two studies compared FCM, ferric derisomaltose (FDI), and IS; one study compared FCM, iron dextran (ID), and IS; one study compared FCM, IS, ID, and FDI at three dose levels; one study obtained an economic ranking for FCM, ID, IS, and ferrous gluconate (FG); five studies compared FDI and FCM; and one study compared FDI with IS. The overall quality of the included studies was high. A total of 13 studies conducted sensitivity analyses to check the robustness of their results.ConclusionThis review systematically evaluates the economic characteristics of the six main intravenous iron formulations for treating IDA. Current evidence suggests that the efficacy of FDI is better than IS, and the economic ranking of the four intravenous iron formulations can be summarized as FCM, ID, IS, and FG. Further research is needed to justify the economic comparison between FCM and FDI.